انعكاسات تقلبات أسعار النفط على السياسة املالية في الجزائر من سنة : 2000 إلى 2020" دراسة قياسية" - مروى حزايمية; عبير بن معنصر (My University, 2024)
This study aims to know the impact of oil price fluctuations on Algeria’s financial policy, based on data from the period (2000-2020), which depends on the export of one commodity, which is oil, as the Algerian economy is knownas a rentier economy because it relies heavily on petroleum revenues. The reality of financial policy was also presented in Algeria, through the changes that occur in oil prices, including rise and fall in global markets, and highlighting the status and importance of oil in the Algerian economy. The result obtained, using the Eviews program, indicates that there is a direct relationship between oil prices, public expenditures, and public revenues, as the increase Oil prices at one dollar lead to positive effects on financial policy tools, and decision makers follow a contractionary policy in the event of a decline in oil prices, and in the event of an increase, an expansionary policy is followed, which indicates that the financial policy followed by decision makers follows cyclical trends. تهدف هذه الدراسة إلى معرفة أثر تقلبات أسعار النفط على السياسة المالية للجزائر بالاعتماد على البيانات من الفترة (2000_ 2020) والتي تعتمد على تصدير سلعة واحدة ،إذ يعرف الاقتصاد الجزائري بالاقتصاد الريعي لاعتماده بشكل كبير على العوائد البترولية وكما تم عرض واقع السياسة المالية في الجزائر من خلال التغيرات التي تطرأ على أسعار البترول في الاقتصاد الجزائري فقد كانت النتيجة المتوصل إليها باستخدام برنامج eviews10 تشير إلى وجود علاقة طردية بين أسعار النفط والنفقات العامة حيث أن زيادة أسعار النفط بواحد دولار تؤدي إلى أثار إيجابية على أدوت السياسة المالية على أدوات السياسة المالية وأن إتباع سياسة توسعية مما يدل أن السياسة المالية المتبعة من طرف أصحاب القرار تتبع الاتجاهات الدورية. الكلمات المفتاحية: السعر النفطي، السوق النفطية ، الأزمات النفطية والسياسة المالية
Keywords: Keywords: oil price; oil market; oil crises and financial policy; Mots clés : prix du pétrole; marché pétrolier; crises pétrolières et politique financière